SME relationship banking and loan contracting: Survey-based evidence from China - Shun Lu; Marina Glushenkova; Wei Huang; Kent Matthews (Cardiff University, Cardiff Business School, 2024)
This study explores the impact of relationship banking on the financial constraints and loan conditions of small and medium-sized enterprises (SMEs) in China. Our research contributes to the literature in several ways. First, we examine both the financial costs and loan benefits associated with SME relationship banking, extending the scope of existing literature. Second, our study is unique in its focus on micro-enterprises, rather than large-scale listed companies in China. Lastly, we enhance the quality of the analysis by using direct measures of firms' spending on bank relationships and their financial constraints, drawn from a recent survey on SMEs in China. Our findings are twofold. On one hand, bank relationship spending significantly reduces financial constraints for SMEs by facilitating access to loans. On the other hand, while this spending enables SMEs to secure more bank credit and longer-term loans, it also results in higher interest rates, increased guarantee requirements, and overall dissatisfaction with loan services. Our research provides new insights into the role of 'guanxi' in China's credit market and its consequences.
Keywords: G21; L14; O53; 330; SME Financing; Relationship Banking; China; Financial Constraints